Electronic brace for the measurements and eliciting of muscle contractions in a dog's ankle - Bunc, Matjaž (Informacije MIDEM, 2001)
An experimental electronic brace, which is able to avaluate torque in the ankle joint of a dog elicited by spontaneous or stimulated muscle contraction,has been developed. The brace is aslo able to impose electrically controlled passive movements on the dog leg. Precise-passive movements, as passive external, electrically-controlled flexion or extension of the ankle ofa dog leg, are defined in as speed and angle of rotation / movement. On the other hand, switching in a certain working mode, the brace, equipped with force transducers and a goniometer, could serve for measurements of isometric (locked mode) or isotonic contractions (active mode and passive mode) of a dogleg. A range of the rotation around the ankle joint is limited between -40 and +55 degrees according to the neutral position. The calculated endurance moment of the brace is 2.41 x 10-4 kg m2 s-1, while the speed of electronically controlled movement of the brace in the passive mode is up to 78 degrees/second, respectively. In the active mode the brace is able to rotate synchronously with the dog ankle joint with a speed of up to 400 degrees/second. The maximum frequency, on activation of the tibialis anterior muscle current, when the amplitude of flexion was 50 degrees, was 7/min. In the locked mode the brace is able to measure the amplitude of force of a dog leg isometric contraction elicited by electrical stimulation. The force transducer with a natural frequency of 8 Hz and compliance of 0.4 um/g represents a very linear dependence of the output voltage upon the load with atransducer sensibility of 0,5 mV/mN at a bridge excitation voltage of 5V. Thenominal range of each transducer is 0-70 N.
Keywords: Ankle joint; Dogs; Electric stimulation therapy; fiziologija; gibanje; Muscle contraction; noga; opornica; Orthotic devices